Resolving the Durand Conundrum - Lou Burnard (OpenEdition, 2017)
This paper proposes a minor but significant modification to the TEI ODD language and explores some of its implications. Can we improve on the present compromise whereby TEI content models are expressed in RELAX NG? A very small set of additional elements would permit the ODD language to cut its ties with any existing schema language, and thus permit it to support exactly and only the subset or intersection of their facilities which makes sense in the TEI context. It would make the ODD language an integrated and independent whole rather than an uneasy hybrid, and pave the way for future developments in the management of structured text beyond the XML paradigm.